Geocultural Power: China's Belt and Road Initiative. Issue 5 (4th October 2021) - Winter, Tim
ABSTRACT: This paper examines China's Belt and Road Initiative as an exercise in geocultural power. To date, Belt and Road has been analysed as a geopolitical and geo-economic initiative, with arguments constructed around the development of infrastructure, trade or finance agreements. This paper introduces the Silk Roads as one of the most compelling geocultural concepts of the modern era to show its strategic value as a platform for cooperation and multi-sector connectivity. A critical analysis of the Silk Roads provides new insights into Belt and Road, revealing how China is mobilising its geocultural potential as a civilisational state to build regional and continental connectivities.